Puding Kelor sebagai Pangan Lokal Bergizi Pendukung Pencegahan Stunting di Desa Mlese - Isnandhani Rasyid Karimanudin; Winingsih Winingsih; Rajendra Adam Cahya Putra; Sherly Anggara Dyah Pratiwi; Novia Eka Yuliana; Alfin Risky Firmansyah; Intan Gustinasari; Rofida Anggun Wulandari; Endri Wahyu Ningsih; Shafa Salsabila Arianto; Muh. Naufal Ainur Imam; Reno Nurdiyanto; Rahma Mutiara As`syifa (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Stunting remains a nutritional problem in Klaten Regency, with a prevalence of 13.9% in 2025. According to information from the Head of the Village Health Forum of Mlese Village, one toddler is still identified as being at risk of stunting. This community service program aimed to educate the community on the utilization of Moringa oleifera leaves as an alternative supplementary feeding (PMT) by preparing moringa pudding. The program employed the Participatory Action Research (PAR) method through coordination, educational sessions, demonstrations of moringa pudding preparation, and product distribution to mothers with toddlers. The results showed that participants gained an understanding of the nutritional benefits of moringa leaves and their processing into pudding. Participants also showed enthusiasm by actively engaging in discussions, asking questions, and tasting the distributed product. This program demonstrates that moringa pudding has the potential to support stunting prevention through the utilization of local food resources.